2020
DOI: 10.3897/zookeys.1002.53988
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians and reptiles of Parque Nacional da Serra das Lontras: an important center of endemism within the Atlantic Forest in southern Bahia, Brazil

Abstract: Information gaps about species distribution hamper the evaluation of conservation status and decisions on biodiversity conservation, affecting to a greater extent, areas with high species richness and endemism. In this context, biological inventories are an important tool to fill these gaps by providing data on the composition, richness, and abundance of species in each locality. The Parque Nacional da Serra das Lontras (PNSL) protects various mountain range just up 1000 m. in altitude, and, together with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
(69 reference statements)
2
7
0
1
Order By: Relevance
“…The two amphisbaenian species identified in our study are common and frequently recorded in the Atlantic Forest inventories from the Brazilian northeast (Couto-Ferreira et al 2011;Freitas et al 2018;Mesquita et al 2018). Despite the fossorial habit of the group, the number of species recorded in our study was similar to that recorded in other studies in the Atlantic Forest (Santana et al 2008;Roberto et al 2017;Rojas-Padilla et al 2020). Perhaps the long-term fieldwork and the use of different methods of data collection have been important to record these organisms.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The two amphisbaenian species identified in our study are common and frequently recorded in the Atlantic Forest inventories from the Brazilian northeast (Couto-Ferreira et al 2011;Freitas et al 2018;Mesquita et al 2018). Despite the fossorial habit of the group, the number of species recorded in our study was similar to that recorded in other studies in the Atlantic Forest (Santana et al 2008;Roberto et al 2017;Rojas-Padilla et al 2020). Perhaps the long-term fieldwork and the use of different methods of data collection have been important to record these organisms.…”
Section: Discussionsupporting
confidence: 85%
“…Observing the richness of only the assemblages within the State of Bahia, the richness found in the present study was inferior to the richness of lizards from the northern coast (Couto-Ferreira et al 2011, n = 23), Serra da Jibóia (Freitas et al 2018, n = 19), and Serra do Timbó (Freitas et al 2019, n = 19). However, the richness of Cruz das Almas lizards was higher than that recorded for nine sand dunes of the southern and northern coast of Bahia (Dias and Rocha 2014, n = 4-11), mountainous forests in southern Bahia (Rojas-Padilla et al 2020, n = 7), fragments of ombrophilous forest of southeast Bahia (Dias et al 2014b, n = 3 or 4), and the semideciduous seasonal forest of southeast Bahia (Souza- Costa et al 2020, n = 6). Although the richness estimators revealed that there are lizard species that have not yet been sampled in the Cruz das Almas assemblage, their values were low, indicating that there may be few species.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Studies with diverse groups of organisms found AoE similar to our data, such as those for angiosperms (Prance, 1982;Thomas et al, 1998;Tabarelli et al, 2005;Murray-Smith et al, 2008;Sigrist and Carvalho, 2008;Werneck et al, 2011;Menini-Neto et al, 2016;Ostroski et al, 2020), amphibians (Rojas-Padilla et al, 2020, arthropods (Sigrist and Carvalho, 2008;Hoffmeister and Ferrari, 2016), bees (Garraffoni et al, 2017), beetles (Silva and Vaz-de-Mello, 2020), birds (Silva et al, 2004), harvestmen (Da Silva et al, 2015, reptiles (Rojas-Padilla et al, 2020) and other vertebrates (Tabarelli et al, 2005;Sigrist and Carvalho, 2008).…”
Section: Generalized Areas Of Endemismsupporting
confidence: 86%